The Effect of Snakehead Fish (Channa striata) Extract on Dry Socket Wound Healing: TGF-β1 Expression in Rats Model - HG, Afifah Ayuni; Syafruddin Ilyas; Olivia Avriyanti Hanafiah (HM Publisher, 2024)
Background: Dry socket or alveolar osteitis is a condition characterized by the breakdown of blood clots due to excessive fibrinolysis activity, which disrupts the wound healing process. Consumption of nutrition-rich foods such as snakehead fish (Channa striata) rich in albumin, omega-3 fatty acids, vitamins, minerals, and striatin may accelerate delayed wound healing. This study aimed to analyze the role of snakehead fish extract on the expression of TGF-β1 in the healing of dry socket wounds after tooth extraction in Wistar rats. Methods: This study was an in vivo study with a posttest-only control group design. Forty-five Wistar rats were divided into five groups: snakehead fish extract groups with doses of 1/2, 1, 2, 4 times human dose, and a negative control. The lower left incisor teeth of the rats were extracted, then dry socket was induced with adrenaline using a paper point. On days 3, 7, and 14, TGF-β1 expression was assessed using immunohistochemical staining. Results: This study showed significant difference in TGF-β1 expression on days 3, 7, and 14. TGF-β1 expression was higher in the treatment groups than the control (p<0.05). Conclusion: Administration of snakehead fish extract increased TGF-β1 expression. These findings underline the complex interaction between snakehead fish extract and TGF-β1 expression.